PRODUK FERMENTASI IKAN DARI CACING KAPAL Bactronophorus sp SEGA - DENNY SYAPUTRA; B. IBRAHIM; D. POERNOMO (Akuatik: Jurnal Sumberdaya Perairan, 2007)
Fish processing method by decreasing pH value has been practised by people who live in South East Asia region for so long, including Indonesia. High biodiversity of fish species in tropical water, which motivated the researcher to do investigation on fish processing using these raw materials. Thus, it would be interesting investigation because shipworm as raw material for making a fermentation product need to be learnt so that it would be an alternative choice beside the others well-known consumed fermentation products like fish sauce, belacan, and bekasam. Shipworm specialized as wood-borer, which use brackish water drawned-dead bakau wood as it main food. Shipworm in this investigation by catched in mangrove forest in Tanjung Batu village, subdistrict of Belinyu, Bangka regency, wich well-known as temilok. The average of rendement of fresh temilok is 94.87%, with water content 73.60%, ash 1.04%, protein 4.29%, and fat 4.05% (with TVB value 10.6 mg N/ 100 gram sample). The best fermented temilok is made by adding the fresh temilok with 10 % salt, and ambient temperature for 20 days, which interesting produce distictive flavor and good taste. The water content of end product is 66.06%, ash 10.85%, protein 5.51%, and fat 0.76%. Colony of bacteria counted with Total Plate Count method is 5.7 x 104 colony/ gram, and pH is 4.55.